(untitled) (Journal of Engineering, 2006)
This study included three trials that were made during December 2003 by using lime, of 98% w/w calcium hydroxide to find the relation between lime doses to be added and the hardness removed .The trials were performed by adding various doses of lime and measuring the hardness, electrical conductivity and pH in water produce by three plants, Nissan in the north of Baghdad, Al-Karama and Al-Wathba water treatment plant in Baghdad center. The objective of this study is to find the optimum lime dose that gives the minimum hardness content. The results indicate a non linear relation between lime dose added and the hardness removed . The results represented a 36% removal in hardness when using an optimum dose of lime 200 ppm in Nissan water treatment plant, while a percentage removal of 34% was obtained in both Al- Karama and Wathba water treatment plants with 300 ppm dose of lime. The low percentage removal indicates the presence of non-carbonate hardness which could not be removed by lime alone.